External kin, economic disparity and minority ethnic group mobilization. (February 2014) - Han, Enze; O'Mahoney, Joseph; Paik, Christopher
What is the relationship between economic grievance and ethnopolitical conflict? Many theories on ethnic conflict posit a relationship between economic inequality and conflict, and many tend to agree that economic inequality between groups is one of the main causes of grievance and thereby political mobilization. This article engages existing literature on horizontal inequalities, but probes the violent consequences of a different type of economic inequality. In particular, we are interested in the type of ethnic group that has extensive external kin relations, and how in such conditions the economic disparity between the ethnic group and its external kin group condition the former's grievance construction. We argue that, if the ethnic group's external kin enjoys positive economic advantage over the ethnic group, then the latter is more likely to feel deprived and engage in violent political mobilization toward the current host state.